The influence mechanism underlying meaning in life on career adaptability among college students: a chain intermediary model - Lin, Zhengzheng (Frontiers in Psychology, 2024)
Introduction The coronavirus disease 2019 (COVID-19) has posed a huge challenge to the career situation of college students. This study aimed to understand the mechanism underlying meaning in life on career adaptability among college students during the COVID-19 pandemic. Methods A quantitative method was adopted. In total, 1,182 college students were surveyed using the Meaning in Life Questionnaire, the Simplified Coping Style Questionnaire, the Adult General Hope Scale, and the Career Adapt-Abilities Scale. Results There was a significant positive correlation between meaning in life, positive coping styles, hope, and career adaptability. Positive coping styles and hope play a separate mediating role and a chain mediating role. Discussion The findings of this study emphasize the importance of meaning in life among college students to improve their career adaptability. Furthermore, positive coping styles and increased levels of hope contribute to the development of career adaptability among college students.